Serum Golgi protein 73 (GP73) is a diagnostic and prognostic marker of hepatocellular carcinoma - Qian Wang; Hongxia Cui; Yaping Zhu; Yichun Zhu; Chunyan He (Frontiers in Medicine)
IntroductionHepatocellular carcinoma (HCC) constitutes a significant global health burden, and is characterized by limited early detection methods and poor survival rates. Golgi protein 73 (GP73), previously associated with liver-related diseases, has a controversial diagnostic value for HCC. The present study aimed to determine the diagnostic efficacy of serum GP73 (sGP73) levels in HCC and to explore their potential correlations with the development of HCC.MethodsThe levels of sGP73 and serum alpha-fetoprotein (sAFP) were measured in 134 HCC patients, 200 healthy controls (HCs), and 45 non-HCC patients with various liver diseases. Additionally, immunohistochemical staining was conducted on paraffin-embedded tissue samples obtained from 30 HCC patients to examine the expression of CD4+ T cells, CD8+ T cells, Foxp3+ Treg cells, Ki-67, and interferon-gamma (IFN-γ) in the tissue specimens.ResultssGP73 and sAFP were markedly higher in HCC patients than in HCs and non-HCC patients. However, sGP73 showed significantly higher sensitivity as a diagnostic marker for HCC than sAFP. The combination of sGP73 and sAFP further improved the accuracy (AUROC: 0.830). Besides, in the immunohistochemical staining analyses, sGP73-positive patients had lower expression of CD4+ and CD8+ T cells, higher expression of Foxp3+ Treg cells, higher expression of nuclear Ki67, and lower expression of IFN-γ than GP73-negative patients. In addition, sGP73-positive patients tended to have higher mortality rate, higher rate of metastasis, higher AFP levels, and more pronounced liver inflammation and damage than GP73-negative patients.ConclusionssGP73 could be utilized as a marker for the diagnosis of HCC, and may be implicated in the development of HCC through its interactions with the tumor microenvironment.